Thermal stability and electrochemical behavior of commercial polycrystalline and single-crystalline cathodes integrated with cubic Li6.4La3Zr1.4Ta0.6O12 for all-solid-state lithium batteries - Ma, Ziting; LaBriola, Grant; Salazar, Karlo Adrian; Mi, Chunting Chris; Kong, Lingping (Journal of materials chemistry. A, Materials for energy and sustainability, 2025)
All-solid-state lithium batteries (ASSLBs) have emerged as promising next-generation energy storage systems, offering enhanced safety and higher energy density compared to conventional Li-ion batteries. However, their practical performance remains limited by interfacial instabilities. In this work, we systematically investigate the interfacial reactions and secondary phase formation between garnet-type cubic Li6.4La3Zr1.4Ta0.6O12 (LLZTO) and a variety of commercial cathode materials, including polycrystalline LiNi0.5Mn1.5O4 (pc-LNMO), LiCoO2 (pc-LCO), LiNi1−x−yMnxCoyO2 (pc-NMC811, 631, 532, 111), and single-crystalline NMC631 (sc-NMC631). Structural analyses reveal that interfacial phase evolution is highly dependent on cathode composition, crystal structure, and sintering temperature. Among all compositions studied, sc-NMC631 exhibits superior thermal compatibility with LLZTO, maintaining phase integrity up to 1000 °C. In contrast, polycrystalline cathodes undergo distinct interfacial degradation: La2Zr2O7 and LaCoO3 form at 700 °C in pc-LCO + LLZTO, while Li2MnO3 and La2Zr2O7 emerge as early as 400 °C in pc-LNMO + LLZTO. In pc-NMC + LLZTO composites, LaMO3-type (M: Ni, Mn, Co) phases are consistently observed. Additionally, La2(Ni0.5Li0.5)O4 phase is present in these Ni-rich compositions and Li2MnO3 is in the Ni-lean NMC111. Electrochemical studies reveal a 63% capacity loss in pc-NMC631 + LLZTO-900, primarily due to resistive interfacial phases and poor solid–solid contact that impede Li-ion transport. In comparison, sc-NMC631 + LLZTO-900 demonstrates a lower capacity loss of 48%, attributed to enhanced interfacial stability over its polycrystalline counterpart. However, the remaining capacity loss is likely due to misaligned Li-ion transport pathways across the rigid solid–solid interface. These results highlight the critical role of cathode selection and interface engineering in garnet-based ASSLBs and establish sc-NMC631 as a promising candidate for high-performance composite cathodes.